2019
DOI: 10.1039/c9tb01299k
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial photochemotherapy on liver cancer stem cells with organoplatinum(ii) metallacage-based nanoparticles

Abstract: Metallacage-based nanoparticles have superior therapeutic performance against liver cancer stem cells in both traditional 2D model and 3D multicellular spheroids, providing a promising strategy for efficient cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Another study utilized silver nanoparticles as a catalyst for ROS over-production to modify gene expression and protein alteration in mouse embryonic stem cells, affecting their self-renewal and proliferation capacity [ 72 ]. Moreover, organoplatinum (II) metallacage-loaded nanoparticles demonstrated their ability to inhibit liver CSC spheroid formation under near-infrared laser irradiation by generating ROS, resulting in the disruption of MMP, causing damage to the mitochondrial membrane, and triggering cell apoptosis [ 73 ]. According to the aforementioned findings, we strongly recommend the use of TiOxNPs as a synergistic drug with radiation therapy to eradicate pancreatic CSCs and inhibit EMT and metastasis through the over-production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study utilized silver nanoparticles as a catalyst for ROS over-production to modify gene expression and protein alteration in mouse embryonic stem cells, affecting their self-renewal and proliferation capacity [ 72 ]. Moreover, organoplatinum (II) metallacage-loaded nanoparticles demonstrated their ability to inhibit liver CSC spheroid formation under near-infrared laser irradiation by generating ROS, resulting in the disruption of MMP, causing damage to the mitochondrial membrane, and triggering cell apoptosis [ 73 ]. According to the aforementioned findings, we strongly recommend the use of TiOxNPs as a synergistic drug with radiation therapy to eradicate pancreatic CSCs and inhibit EMT and metastasis through the over-production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentration was measured by Bradford assay (Bio-Rad Laboratories, Inc., Hercules, USA). Western blots were performed as previously described [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effect of ROS on the function of mitochondria has always been one of the research focuses of CSCs. ROS produced through PDT can induce apoptosis through increased mitochondrial membrane potential[ 111 ]. Studies have shown that mitochondrial photooxidative stress can cause a large number of lipid peroxidation reactions in the mitochondrial membrane, leading to rapid changes in the MMP, which stimulates pressure-dependent anion channels [voltage-dependent anion channels (VDACs)][ 112 ] and promotes the opening of the permeability transition pore complex[ 113 , 114 ], thereby releasing cytochrome C (Cyt C)[ 115 , 116 ] into the cytoplasm.…”
Section: Impact Of Ros From Pdt On Cscsmentioning
confidence: 99%